Evaluation of Thiosulfate for Gold Recovery from Pressure Oxidation Residues - Christiana Mystrioti; Konstantina Kousta; Nymphodora Papassiopi; Katerina Adam; Maria Taxiarchou; Ioannis Paspaliaris (Materials Proceedings)
This paper investigated the potential of thiosulfate as an alternative to cyanide for gold recovery from pressure oxidation residues. Thiosulfate leaching experiments were conducted under controlled conditions, varying parameters such as initial thiosulfate concentration, initial pH, temperature and solid–liquid mixing ratio (S/L). The results indicate that thiosulfate demonstrates promising gold recovery rates, with optimization potential through parameter adjustments. This study aimed to provide valuable insights into the feasibility of adopting thiosulfate as a gold recovery agent, promoting environmentally responsible practices in the metallurgical industry while addressing the challenges associated with pressure oxidation residues.